Palm Oil Supply Chain Analysis : Village Potential In Processing Factories In East Halongonan District, North Padang Lawas Regency - Ningsih, Nova Ayu; Hasanah, Uswatun; Fadlan, Ahmad (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to analyze the influence of the palm oil supply chain in developing village potential in processing factories in East Halongonan District, North Padang Lawas Regency. This study uses a quantitative approach applied to time-series data from 2015 - 2024 with secondary data from the Central Statistics Agency which is analyzed using Multiple Linear Regression techniques after fulfilling classical assumption tests such as normality, multicollinearity and heteroscedasticity. The results of this study's analysis indicate that partially Land Area (X1) has a positive and significant effect on GRDP (Y) with a calculated t-value of 5.671> t-table 2.01 and sig. 0.03 <0.05. Production Amount (X2) also has a positive and significant effect on GRDP (Y) with a calculated t-value of 7.360> t-table 2.01 and sig. 0.02 <0.05. Production Selling Price (X3) also has a significant effect on GRDP (Y) with a t-count of 6.872 > 2.01 and sig. 0.01 < 0.05. The Number of Workers also has a significant effect on GRDP (Y) with a t-count of 4.313 > 2.01 and sig. 0.04 < 0.05. Simultaneously, the four variables show an F-count of 16.739 > F-table of 5.19 and sig. 0.00 < 0.05 with a coefficient of determination of 87.5% which explains the variation in GRDP, the rest is influenced by external factors of 12.5%.